The Parkinson's disease‐associated GPR37 receptor‐mediated cytotoxicity is controlled by its intracellular cysteine‐rich domain. (3rd March 2013) - Gandía, Jorge; Fernández‐Dueñas, Víctor; Morató, Xavier; Caltabiano, Gianluigi; González‐Muñiz, Rosario; Pardo, Leonardo; Stagljar, Igor; Ciruela, Francisco
Abstract: GPR37, also known as parkin‐associated endothelin‐like receptor (Pael‐R), is an orphan G protein‐coupled receptor (GPCR) that aggregates intracellularly in a juvenile form of Parkinson's disease. However, little is known about the structure or function of this receptor. Here, in order to better understand the functioning of this receptor, we focused on the GPR37 C‐terminal tail, in particular on a cystein‐enriched region. Thus, we aimed to reveal the role of these residues on receptor plasma membrane expression and function, and also whether the presence of this cysteine‐rich domain is linked to the previously described receptor‐mediated cytotoxicity. Interestingly, while the deletion of six cysteine residues within this region did not affect receptor internalization it promoted GPR37 plasma membrane expression and signaling. Furthermore, the removal of the C‐terminal cysteine‐rich domain protected against GPR37‐mediated apoptosis and cell death. Overall, we identified a GPR37 domain, namely the C‐terminal tail cysteine‐rich domain, which played a critical role in receptor cell surface expression, function and GPR37‐mediated cytotoxicity. These results might contribute to better comprehend the pathophysiology (i.e. in Parkinson's disease) of this rather unknown member of the GPCR family. Abstract : GPR37 is a rather unknown orphan GPCR that in a genetic form of Parkinson's disease accumulates intracellularly and induces neuronal death. In this study, we describe a cystein‐rich domain in the C‐terminal tail of the receptor that controls its membrane expression and whose absence reduces the GPR37‐dependent citotoxic effects on ER stress and cell death.